Flash-Sintering and Characterization of La0.8Sr0.2Ga0.8Mg0.2O3-δ Electrolytes for Solid Oxide Fuel Cells. (1st April 2016) - Sun, Kening; Zhang, Jing; Jiang, Taizhi; Qiao, Jinshuo; Sun, Wang; Rooney, David; Wang, Zhenhua
Highlights: A current-limiting flash-sintering technique was developed for LSGM densification. LSGM was densified by the current-limiting flash-sintering process at 690 °C. The conductivity sintered at 0.9 A was comparable to that conventionally sintered. Abstract: La0.8 Sr0.2 Ga0.8 Mg0.2 O3-δ (LSGM), a promising electrolyte material for intermediate temperature solid oxide fuel cells, can be sintered to a fully dense state by a flash-sintering technique. In this work, LSGM is sintered by the current-limiting flash-sintering process at 690 °C under an electric field of 100 V cm −1, in comparison with up to 1400 °C or even higher temperature in conventional furnace sintering. The resultant LSGM samples are investigated by scanning electron microscopy, X-ray diffraction, and electrochemical impedance spectroscopy. The SEM images exhibit well-densified microstructures while XRD results show that the perovskite structure after flash-sintering does not changed. EIS results show that the conductivity of LSGM sintered by the current-limiting flash-sintering process increases with sintering current density value. The conductivity of samples sintered at 120 mA mm −2 reaches 0.049 σ cm −1  at 800 °C, which is approximate to the value of conventional sintered LSGM samples at 1400 °C. Additionally, the flash-sintering process is interpreted by Joule heating theory. Therefore, the current-limiting flash-sintering technique is proved to be an energy-efficient and eligible approach for the densification of LSGM and other materials requiring high sintering temperature.